Social Load and Career: An Analysis of Gendered Factors Affecting the Career Progression of Female Managers in the Hospitality Industry - Aslı Ersoy; Vesile Rüya Ehtiyar (Journal of Economy Culture and Society)
This study aims to discover the effect of gender-related thoughts and perceptions of female managers in the hospitality industry on their career progression and to uncover the experiences and difficulties that gender perceptions cause them during their careers. For this purpose, we used convenience sampling to select 14 female managers who were employed in various positions at hospitality businesses operating in central Antalya. In-depth interview technique and semi-structured interview form were used to collect the research data. The study was conducted within the scope of phenomenological design, which is one of the qualitative research designs. The content analysis technique and QSR NVivo 10 qualitative analysis software program were used to analyze the research data. In the research, the following five categories were determined: opinions on career opportunities for women in Turkey, factors hindering women’s career advancement in the hospitality industry, behavioral methods of coping with industry-related challenges for women, factors facilitating women’s career development, and opinions on the equality of opportunity between men and women. Based on the five aforementioned categories, 28 conceptual codes were obtained. When the obtained data was evaluated as a whole, we could conclude that gender roles affect the career processes of female managers. Nevertheless, the research determined that women can fulfill multiple roles, they do not prefer giving up despite all the difficulties and obstacles, and they prefer to progress and struggle in their careers.